Toxicological Risk Assessment for Beginners - Torres, José A.; Bobst, Sol (Springer International Publishing : Imprint: Springer, 2015)
This book serves as a comprehensive introductory guide to the practical aspects of risk assessment. Chapters include clearly defined objectives and summaries.  The book includes:  hazard identification, dose-response, exposure assessment, risk characterization, chemical mixtures, epidemiology, emerging issues and global perspectives with accessible language.  The book concludes with a set of hypothetical case studies. Toxicological Risk Assessment for Beginners aims not to create an expert, but rather to provide readers with their first understanding of the risk assessment topic. This book was designed with the student in mind.  We simplify a complex process for beginners and balance theory with practical aspects, but remain fluid enough to increase difficulty with case studies.  By incorporating an action based, step by step approach to learning the risk assessment process, this book provides its readers with an elementary understanding of how the risk assessment process is initiated, developed and finished, making it a valuable guide for graduate students, post-doctoral fellows and early career scientists in industry.